homehelper
homehelper
02-01-2017
Mathematics
contestada
solve by elimination -2x - 6y = 0 3x +11y=4
Respuesta :
xXPeachXx
xXPeachXx
02-01-2017
Work
-2x - 6y = 0
3x + 11y = 4
Either y or x must be a negative.
If x is -6, and y is 2 then
(-2 · -6) - (6 · 2) = 0
12 - 12
and
(3 · -6) + (11 · 2) = 4
-18 + 22
Answer
x = -6
y = 2
Answer Link
VER TODAS LAS RESPUESTAS ( 85+ )
Otras preguntas
please give me the answer of the blanks
The radius of the front wheel of Jordan's bike is 53cm. Jordan goes for a cycle and travels 53.23km. How many full revolutions did Jordan's front wheel complet
y= 4x^2-8x+9 find the vertex, domain, and range.
How does Mutation occurAnd its affect on evolution
Balancing Chemical Equations
Johnny says that rolling a number cube twice and getting a 6 both times is an example of dependent events because getting a 6 on the second roll depends on gett
[HELP!!] A circle has a radius of 6 ft. What is the area of the sector formed by a central angle measuring 5π3 radians? Use 3.14 for pi.
How would you describe America’s problem with race?
How would you figure this out? (screen shot included)
a composition in French to describe your father